PROFIL PENERIMAAN DIRI MAHASISWA CALON PENDIDIK DAN IMPLIKASINYA BAGI LAYANAN BIMBINGAN PRIBADI : Studi Deskriptif terhadap Mahasiswa Calon Pendidik Fakultas Ilmu Pendidikan Universitas Pendidikan Indonesia Angkatan 2018 - Arnik Agniya Fikriyah, - (2019)
Arnik Agniya Fikriyah. (2019). Profile of Self-Acceptance in College student Candidates for Educator and the Implications for Personal Guidance Services. (Descriptive Study in College student Candidates for Educator in the Faculty of Education UPI at class 2018). This research is motivated by a phenomenon that students feel inferior in relationships, embarrassed because they are not the same as the conditions of others, lack confidence in their abilities and physical appearance and there are still students who are not brave enough to express his opinion. This study aims to determine the description of self-acceptance of college student candidates for educators of the Faculty of Education UPI 2018 and produce a program of personal guidance services. Through the personal guidance program that has been made, it is expected that the ability of self-acceptance of college student candidates for educators of the Faculty of Education UPI 2018 can be improved. This research was conducted using quantitative approaches and descriptive methods. Analysis of this research data using the Rasch Model. The results of the research that the self-acceptance profile of college student candidates for educators of the Faculty of Education UPI 2018 are in the conditional self-acceptance category. That is, most of the self-acceptance of college student candidates for educators of the Faculty of Education UPI 2018 are able to accept themselves. Keywords: self-acceptance, college student, Personal Guidance